Hands, Eyes, Ceramics : Een publicatie bij Kamer vol klei - Waegemans, Liesbet (Gent : MER. B&L, 2023)
Vandeweghe, Rogier ; Culot, Pierre ; De Meyer, Lutgart ; Vermeersch, José ; Doyen, Nathalie ; Michels, Bie ; Ausloos, Anne ; Engelfriet, Alexandra
Kamer vol klei, Museum Albert Van Dyck, Schilde, 28 februari tot 4 juni 2023
boek